Identification of the novel HLA‐B*50:18 allele variant in an Italian unrelated bone marrow donor. Issue 6 (6th May 2013) - Azzarone, R.; Canossi, A.; Cervelli, C.; Scimitarra, M.; Papola, F.
Abstract : The HLA‐B*50:18 allele differs from the closest related B*50:01:01 by one nucleotide substitution at position 454 in exon 3.